Home Gardens, Local Knowledge, and Public Health: The Distinctive KESURGA Approach to Stunting Reduction - Dewi Ayu Hidayati; Suwarno Suwarno; Yuni Ratna Sari; M Eki Pratama; Komang Ariyanto (Yayasan Keluarga Guru Mandiri, 2025)
Stunting is a growth failure condition caused by inadequate nutrition during a child's developmental years. In Indonesia, stunted toddlers are prevalent, particularly in Lampung Province, where rates exceed the WHO standard of 20%. In 2019, the Tanggamus region had a stunting prevalence of 27.39%. This study examines the impact of the KESURGA demonstration plot intervention, which aims to promote balanced nutrition in Kagungan Village, Kota Agung Timur District, using a qualitative phenomenological approach. Data were gathered through observations, in-depth interviews, and documentation analysis. The findings indicate that the KESURGA intervention, which included training, garden development, and socialization activities, resulted in a reduction in stunting rates from 19.17% in 2020 to 14.18% in 2021. Key supporting factors included effective communication, availability of resources, aligned policies, and positive attitudes. Challenges such as economic conditions of underprivileged families, the Covid-19 pandemic, and a lack of information hindered progress. These results highlight that multi-stakeholder, nutrition-focused interventions can significantly reduce stunting. This study provides qualitative evidence of locally adaptable strategies that contribute to public health nutrition interventions in rural Indonesia, offering insights for global health initiatives. It demonstrates how community-driven, resource-sensitive, and policy-aligned interventions can address malnutrition challenges in low- and middle-income countries.